1968
DOI: 10.1161/01.res.22.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Pressure-Volume Relations and Performance as Affected by Sudden Increases in Developed Pressure

Abstract: Left ventricular performance in the isolated dog heart was observed in a preparation in which left ventricular pressure and volume could be monitored continuously while the ventricle contracted isobarically by compressing air into a large chamber. By suddenly reducing the orifice connecting the ventricle to the chamber a constant load was imposed on the ventricle, abruptly forcing it to develop pressure in systole. This pressure increased over the ensuing 3 minutes while both the load and the end-diastolic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
10
2
1

Year Published

1971
1971
2002
2002

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
3
10
2
1
Order By: Relevance
“…Kanazawa et al reported that close positive correlation between left ventricular diameter and left ventricular segment length obtained as the same manner exists, and that the end-systolic P-L relationship is thus acceptable for estimating ventricular contractility (Suga and Sagawa 1974; Kanazawa et al 1983;Crozatier et al 1984). Aortic constriction has also been used as an experimental procedure for evaluating left ventricular contractility (Monroe et al 1968;Crozatier et al 1984). In the present study, as shown in Figs.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Kanazawa et al reported that close positive correlation between left ventricular diameter and left ventricular segment length obtained as the same manner exists, and that the end-systolic P-L relationship is thus acceptable for estimating ventricular contractility (Suga and Sagawa 1974; Kanazawa et al 1983;Crozatier et al 1984). Aortic constriction has also been used as an experimental procedure for evaluating left ventricular contractility (Monroe et al 1968;Crozatier et al 1984). In the present study, as shown in Figs.…”
Section: Discussionsupporting
confidence: 69%
“…However, another report describes a positive relationship between myocardial norepinephrine depletion and defective myocardial contractility ). Actually, the efferent sympathetic nerve is discharged each beat in situ (Felder and Thames 1981), so norepinephrine deple tion seems to disturb the augmentation of contractility by sympathetic nerve excitation (Covell et al 1966;Monroe et al 1968). Thus, it is quite reasonable to assume that cardiac norepinephrine stores would play an important role in maintaining the cardiac contractile state in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…They, too, dismissed the coronary flow hypothesis of Starling, in view of the findings of Rosenblueth et al (5) and Sarnoff et al (6). As the effect was noted in reserpinized preparations (8,9) they were disinclined to implicate catacholamines in its mechanism. Despite the fact that Sarnoff et al showed an efflux of potassium from the heart after a sudden increase in systolic pressure (10) Blinks and Koch-Weser pointed out differences between the Anrep effect and the Bowditch effect, making it doubtful that similar mechanisms were involved.…”
mentioning
confidence: 97%
“…Later, a report from this laboratory showed the effect to be decreased, but not abolished in an isolated heart preparation treated with propranolol (9). Here it was postulated that at least part of the mechanism could be attributed to catacholamines as norepinephrine has been shown to be released by the ventricle in quantities roughly proportional to systolic pressure (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation